PESANTREN DAN RADIKALISME AGAMA (Studi Kasus Pesantren Hidayatullah Ternate) - Arifuddin Ismail (Al-Qalam, 2007)
This study was conducted in Ternate, North Maluku. The focus study isPesantren Hidayatullah Ternate. This study aims to describe the view ofpesantren community (especially Pesantren Hidayatullah Ternate) onreligion radicalism issue. This study use quantitative and qualitativemethod, where data was collected by using questioner to all studentsand interview to the teachers. The data was analyzed by descriptiveanalysis.This study indicates that the thought expanding among all studentsand teachers is not radical. We can see it from several indicators, suchas; frowning upon hardness, respecting to the others religion followers,and also, concept o/jihad more meant constructively and transformative.The potency expand up at more radical is understanding ofpuritan fundamentalism, such as ban to local culture, stipulating ofwar areas (dar el harb), and textually understanding toAl-Qur 'an verses.